A case study of Pasir Gudang chemical toxic pollution: a review on health symptoms, psychological manifestation and biomarker assessment - Syed Ismail, Sharifah Norkhadijah; Zainal Abidin, Emilia; Rasdi, Irniza (Universiti Putra Malaysia Press, 2020)
Introduction: This paper provides an overview of chemical toxic pollution in Pasir Gudang industrial area Johor Malaysia. It discussed the health symptoms, argument of the psychology manifestation among children and the application of biomarkers and monitoring systems in chemical detection. Methods: The systematic search was conducted for four digital scientific journal databases: Science Direct, SCOPUS, PubMed and Google Scholar with a specified keyword. Results: Seven (7) chemicals were related to this incident namely; Methane, Hydrogen chloride, Acrylonitrile, Acrolein, Benzene, Xylene, and Methyl mercaptan. These chemicals are mainly generated from industrial activity and easily breakdown through interaction with other chemicals and sunlight. Inhalation is the major route of exposure and the major symptoms of these chemicals are headache, nausea, vomiting, breathing difficulties, eye irritation, chest tightness, and wheezing. There is no clear evidence to indicate that the victims in this incident are having a psychological manifestation since all chemicals involved are proven to cause the reported symptoms. Conclusion: Industrial chemicals are potential to produce toxic gas in the air through reaction with other substances or rays and causes acute health symptoms. Diagnose all post-emergency illnesses including mental and physical health is needed. Biomarker testing should consider a specified period after exposure occurs as the reactivity of some types of chemical and its short half-life, rendered limited for use as markers of exposure in the body.